Awareness, concern, and communication between physicians and patients on bone health in cancer. - Tripathy, Debu; Durie, Brian G M; Mautner, Beatrice; Ferenz, Krag S; Moul, Judd W (Supportive Care in Cancer, 2014)
Purpose: This study aims to explore physician-patient communications about bone metastases and cancer treatment-induced bone loss (CTIBL).Methods: The study utilizes online survey of patients with breast cancer, prostate cancer, and multiple myeloma, and the physicians who treat them.Results: Even though 69 and 48 % of patients with nonmetastatic breast and prostate cancer aware of treatment-induced bone loss, only 39 and 23 %, respectively, were concerned about bone loss. Yet, 62 and 71 % of oncologists treating breast and prostate cancer felt that their patients were concerned. Among patients with metastatic breast and prostate cancer, two thirds had not discussed treatment for bone metastases with their doctor; when discussed, 88 and 91 % of discussions were initiated by the doctor, usually prior to initiating treatment. Most myeloma patients (77 %) had discussed treatment options with their physicians; 99 % of hematologists reported discussing treatment of bone disease with patients.Conclusions: Physicians are primary sources of information to patients regarding bone health. There is a gap between what physicians assume their patients know about bone health and the patients' perceptions, presenting a need for systematic awareness and education.